Mid-Proterozoic Evolution of the Grenville Belt: Evidence from Neodymium Isotopic Mapping, Bancroft, Ontario - Martin, Christopher (My University, 1992)
Detailed Neodymium isotopic mapping was performed on grey gneisses from the Algonquin Park area of Ontario, in the Central Gneiss Belt of the southwestern Grenville Province. The Neodymium model ages determined were based upon the Depleted Mantle Model of DePaolo ( 1981c ) . The use of this model is supported by Lead-Lead dating of zircons obtained from an orthogneissic sample.
The wide range of model ages found ( 1.5 - 1.86 Ga ) is attributed to the presence of a northwestward dipping, Andean style, ensialic continental margin arc that was active in the Mid-Proterozoic between 1.50 Ga and 1.65 Ga. The diapiric rise of plutons produced by the subduction zone intruded continental margin at least as old as 1.86 Ga as indicated by the oldest pluton in the field area. Variable amounts of mixing occurred between these orogenic rocks and the existing crustal rocks as illustrated by the variable Neodymium model ages determined for grey gneisses collected between 10 Km and 60 Km north of the Central Metasedimentary Belt Boundary Zone. Major element analysis and subsequent tectonic and petrographic discrimination diagrams such as the AFM plot and the granitoid discrimination diagram of LeFort and Debon ( 1983 ) also indicate that the rocks in the Algonquin Park area are calc-alkaline, and are similar to the Peruvian Coastal Batholith.
For grey gneisses analyzed within 10 Km of the Central Metasedimentary Belt Boundary Zone, the range of ages is far more restricted, suggesting that an island arc approximately 1.45 Ga was transported by the subducting slab and later sutured onto the existing continental margin.
Keywords: mid-proterozoic; grenville; neodyium; isotopic mapping; geology